In Search of Likes: Longitudinal Associations Between Adolescents' Digital Status Seeking and Health-Risk Behaviors. Issue 5 (3rd September 2019) - Nesi, Jacqueline; Prinstein, Mitchell J.
Abstract : This study introduces a new construct—digital status seeking—which reflects a set of behaviors made possible by the social media environment. Digital status seeking is defined as the investment of significant effort into the accumulation of online indicators of peer status and approval. The concurrent validity of this construct was examined, as well as the longitudinal implications of digital status seeking for adolescents' engagement in health-risk behaviors. A school-based sample of 716 participants ( M age = 16.01 at Time 1; 54.2% female) participated at 2 time points, 1 year apart. Sociometric nomination procedures were used to assess digital status seeking and peer status. Participants self-reported indices of social media use, peer importance, and risky behavior engagement (substance use, sexual risk behavior). For a subset of participants, social media pages were observationally coded for status indicators (i.e., likes, followers) and status-seeking behaviors. Adolescents with greater reputations of digital status seeking reported more frequent social media use, desire for popularity, belief in the importance of online status indicators, and use of strategies to obtain these indicators. Multiple group path analyses indicated that for both genders, digital status seekers engaged in higher levels of substance use and sexual risk behavior 1 year later. Moderation of this effect by race/ethnicity and socioeconomic status was explored. This novel, multimethod investigation reveals digital status seeking as an important construct for future study and offers preliminary evidence for the unique role of social media experiences in contributing to adolescent adjustment.